Flavonoids From Stems and Leaves of Scutellaria Baicalensis Georgi Improve Composited Aβ-Induced Alzheimer's Disease Model Rats’ Memory and Neuroplasticity Disorders - Zhang, Hui; Liu, Qian-qian; Ding, Sheng-kai; Li, Hong; Shang, Ya-Zhen (Combinatorial Chemistry & High Throughput Screening, 2023)
Aim: The study aims to investigate the effects and mechanism of flavonoids from stems and leaves of Scutellaria baicalensis Georgi (SSF) on the disorders in learning and memory and neuroplasticity induced by beta amyloid 25-35 (Aβ25-35) combined with aluminum trichloride (AlCl3) and human recombinant transfer factor-β1 (RHTGF-β1) (composited Aβ) in rats. Methods: A rat Alzheimer's disease (AD) model was established by intracerebroventricular injection of Aβ25-35 combined with AlCl3 and RHTGF-β1. The successful AD model of rats was screened with a Morris water maze. The successful model rats were randomly divided into a model group and three doses of SSF treated group. The Morris water maze was used to detect the rats’ learning and memory abilities. The real-time fluorescence quantitative (qPCR) was applied to assay the mRNA expressions of CaM, CamkIV and Ferritin, as well as the neuroplasticity factors of HuB, HuC and HuD. The Western blotting was used to measure the protein expressions of CaM, CamkIV, HuB/D, HuC+HuD and Ferritin in the CaM-CamkIV-CREB signal pathway. Results: Compared with the sham group, the abilities of learning and memory in the model group were significantly impaired (P<0.01), and the mRNA or protein expressions of CaM, CamkIV, HuB, HuC, HuD, HuB/D, HuC+HuD and Ferritin in CaM-CamkIV-CREB signal pathway were abnormally changed in model group. However, the three doses of SSF can differently ameliorate the impaired learning and memory and regulate the abnormal expressions of mRNA or protein in rats’ CaM, CamkIV, HuB, HuC, HuD, HuB/D, HuC+HuD and Ferritin induced by composited Aβ. Conclusion: The improvement of SSF on the learning and memory disorder induced by composited Aβ is primarily derived from the positive regulation in the CaM-CamkIV-CREB signal pathway and activation in neuroplasticity.
Keywords: Flavonoids from stems and leaves of Scutellaria baicalensis Georgi